Comparative study of the scientific production in public and private venezuelan universities (Revista Científica Compendium, 2014)
Some universities are seeking ways to generate knowledges that can transform economies and solve many of the conflicts facing society. The objective of this study was to analyze and compare the research activities of public and private universities in Venezuela, regarding the number of publications and degree of participation of each of them in the national scientific production. The investigation was a descriptive and transversal design. A total of 104 Venezuelan journals available in multidisciplinary bibliographic indexes with regional and international significance were consulted. Scientific papers published in 2013 were considered as the unit of analysis, and the participation of researchers, number of published articles, coauthors´ index, and university endogamy were used as indicators. The highest number of participations of researchers belonging to public universities came from medicaljournals, and the lowest from journals on economics sciences. Private universities had lower rates of authorship and higher endogamy index. Public universities showed a greaterorientation towards research and extension while the private ones generally focused onteaching activities. It was concluded that the participation of researchers from public universities far exceeded that of the private universities sector; publications from private institutions occurs mainly in areas where the main resources are represented by computersand specialized literature, and scientific papers are published mainly in journals belonging to the same institution of the researcher.
Keywords: universities; public area; private area; journals